First report of Paysandisia archon on Phoenix theophrasti - Niamouris, Kostas; Psirofonia, Panagiota (ENTOMOLOGIA HELLENICA, 2012)
In March 2012 Paysandisia archon, Lepidoptera: Castniidae, a palm tree pest, was found for the first time in the endemic palm species of Crete Phoenix theophrasti. The infestation was detected in the premises of the Technological Educational Institute in Heraklion, Crete. Information on its biology, morphology and distribution is given.